2017
DOI: 10.1038/cddiscovery.2017.33
|View full text |Cite
|
Sign up to set email alerts
|

Combination of palbociclib and radiotherapy for glioblastoma

Abstract: The cyclin-dependent kinase inhibitor, palbociclib has shown compelling efficacy in breast cancer patients. Several pre-clinical studies of glioblastoma (GBM) have also shown palbociclib to be efficacious. In this study, we investigated palbociclib in combination with radiation therapy (RT) for treating GBM. We tested palbociclib (with and without RT) on four patient-derived cell lines (PDCLs; RB1 retained; CDKN2A loss). We investigated the impact of therapy on the cell cycle and apoptosis using flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 16 publications
3
56
0
1
Order By: Relevance
“…There was also a decrease in the level of total RB after PCB treatment. While the basis for this observation is not clear, it has been reported by others [28,34], and it may reflect diminished levels of RB in G1-arrested cells or be a technical issue with RB phosphorylation influencing antibody affinity. To account for this, the relative levels of RB and phospho-RB were determined by scanning blots from multiple independent experiments.…”
Section: Pcb Induces a Quiescent-like State In Primary All And T98g Cmentioning
confidence: 56%
See 1 more Smart Citation
“…There was also a decrease in the level of total RB after PCB treatment. While the basis for this observation is not clear, it has been reported by others [28,34], and it may reflect diminished levels of RB in G1-arrested cells or be a technical issue with RB phosphorylation influencing antibody affinity. To account for this, the relative levels of RB and phospho-RB were determined by scanning blots from multiple independent experiments.…”
Section: Pcb Induces a Quiescent-like State In Primary All And T98g Cmentioning
confidence: 56%
“…A leading candidate is the highly selective CDK4/6 inhibitor palbociclib (PCB) [24]. PCB received accelerated approval for use in combination with the aromatase inhibitor letrozole or the estrogen receptor antagonist fulvestrant for patients with metastatic HR-positive and HER2-negative breast cancer, and has shown activity in combination with radiotherapy for glioblastoma [25][26][27][28][29]. In this study, we show that PCB has a cytostatic effect on ALL cells, causing G1 phase arrest without reducing viability.…”
Section: Introductionmentioning
confidence: 87%
“…Thus, Palbociclib has not only a cytostatic effect but seemingly a potential cytotoxic effect on CMT cells. Although this observation contrasts to that for human BCa cells, which showed no apoptosis after prolonged Palbociclib treatment, cytotoxic potential for the CDK4/6 inhibitor was reported for human glioblastoma, hepatocellular carcinoma and T‐cell acute lymphoblastic leukaemia cells . Wang et al demonstrated that the pro‐apoptotic Palbociclib effect is associated with CDK6 expression in that Palbociclib induces apoptosis in cancer cells with high expression of CDK6, whereas cells with low CDK6 only show cell cycle arrest .…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, we show that Palbociclib affects ER‐negative CMT cells, although ER expression is suggested to be a marker for Palbociclib responsiveness in hBCa cells . Since the approval of Palbociclib for treating ER‐positive/HER2‐negative hBCa, also oestrogen‐independent, pRb‐positive tumours turned out to be potential Palbociclib candidates, so that currently advanced urothelial cancer, squamous cell lung, pancreatic or head‐and‐neck tumours are under clinical trial (NCT02334527, NCT03065062). Moreover, Palbociclib has activity when combined with endocrine therapy in human patients with mammary tumours that are resistant to such therapy .…”
Section: Discussionmentioning
confidence: 98%
“…Current treatment for malignant glioblastoma including surgery, radiotherapy, and chemotherapy are being applied with limited success (139)(140)(141)(142). GHRH antagonists are being developed to improve the outcome of the treatment to improve the overall survival rate of GMB patients.…”
Section: Discussionmentioning
confidence: 99%